Predictive Models of Word Reading Fluency in Hebrew - Shechter, Adi; Lipka, Orly; Katzir, Tami (Frontiers in Psychology, 2018)
Abstract: This study examined a multi-componential approach to reading fluency in first and third grade Hebrew speaking children. Measures of naming speed, phonological awareness, morphological awareness, morpho-syntax awareness, and vocabulary were administered to first (N=68) and third (N=67) graders. Hierarchical regression models revealed that in both grades, naming speed accounted for most of the variance in each model. However, while in the first grade word reading fluency was also predicted by vocabulary, in the third grade both phonological awareness and morphological awareness were significant additional predictors. Predictive models of word reading fluency in Hebrew and applied implications are proposed.